Adaptive Event-Triggered Consensus of Multi-Agent Systems in Sense of Asymptotic Convergence - Zhicheng Hou; Zhikang Zhou; Hai Yuan; Weijun Wang; Jian Wang; Zheng Xu (Sensors, 2024)
In this paper, the asymptotic consensus control of multi-agent systems with general linear agent dynamics is investigated. A neighbor-based adaptive event-triggering strategy with a dynamic triggering threshold is proposed, which leads to a fully distributed control of the multi-agent system, depending only on the states of the neighboring agents at triggering moments. By using the Lyapunov method, we prove that the states of the agents converge asymptotically. In addition, the proposed event-triggering strategy is proven to exclude Zeno behavior. The numerical simulation results illustrate that the agent states achieve consensus in sense of asymptotic convergence. Furthermore, the proposed strategy is shown to be scalable in case of variable agent numbers.